The role of psychological flexibility in birth experience for first-time mothers: a mixed methods study - Ball, Harriet (2021)
Background: Childbirth is a momentous event for a woman where they can feel empowered and transformed. Negative experiences of birth are linked to development of perinatal mental health difficulties including postnatal depression and birth trauma (Ayers et al., 2016; Bell & Anderson, 2016). Birth can be experienced as negative when birth expectations are not met (Goodman et al., 2004; Hauck et al., 2007). Psychological Flexibility (PF) is a concept adopted within the Acceptance and Commitment Therapy (ACT) model (Hayes et al., 1999). PF could illustrate how a woman adapts to situational demands of birth, shifts perspective or expectations and balances competing wishes and values that encompass expectations of birth. This study aimed to 1) explore the relationships between PF, birth satisfaction and birth expectations, 2) explore whether women report PF-related skills as playing a role in sense-making of birth, and 3) explore what aspects women describe as helping and/or hindering sense-making of birth.